Pengaruh Kepemimpinan Demokratis dan Budaya Organisasi Terhadap Kinerja Pegawai di Kantor Dinas Pariwisata Kabupaten Alor - Theresia Lounggina Luisa Peny (Jurnal Ilmiah Wahana Pendidikan, 2023)
Employee performance is an absolute requirement that must be met in order to achieve company goals. Improving employee performance must be carried out by all components within the company. But so far, in carrying out their duties, employees of the Alor Regency Tourism Office still need to pay attention to optimal performance so that it has an impact on achieving company goals. For this reason, it is necessary to pay attention to the factors of democratic leadership and organizational culture. This study aims to determine the effect of democratic leadership and organizational culture on the performance of Alor Regency Tourism Office employees, either partially or simultaneously. The respondents of this research were 53 employees. Data collection using questionnaires, observation, and documentation studies. From the results of the research and the conclusions of the research, the research team suggested to Respondents (employees of the Alor Regency Tourism Office) that employees are expected to be able to maintain the performance of employees who have been well organized to date, while continuing to improve themselves given the various changes in work situations during the pandemic as happening right now. Suggestions are also given to the Head of the Alor Regency Tourism Office, so that the leaders who have nurtured and built an organizational culture that has been well ingrained in this scope of work can be maintained and by continuing to provide enthusiasm, motivation and innovation for the development of much better employee performance and overall official performance.